Hybrid Cultural Communication Of Postcolonial Society In Cathryn Stockett’s Novel, The Help - Nabiya Rizki Meida; Hawasi Hawasi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This study focuses on hybrid culture communication in the perspective of postcolonialism by using Homi K Bhabha’s theory to understand three characters; Skeeter, Aibileen, and Minnyin CathrynStockett’s novel, The Help. The Help written by Cathryn Stockett tells one of the life aspects of multicultural American society. The novel describes the relationship between black maids and their white households in Mississippi Jackson. By using descriptive-qualitative method the analysis shows that The Help contains a postcolonial elements that can open the ideology of the writer. Those three main characters have their own different identities in language expression and attitude, as process of hybridity occurred between two different races, the black and the white. In the process of hybridity, there is a process of mimicry (including mockery) as experienced by the three characters. They start mimicking without losing their own identities but forming a new identity as the ‘third space’ which is called hybrid culture.